Enamel microabrasion associated with resin infiltration technique: Clinical Report - Rubin Cocco, Alexandra; Chaves Pereira, Jean; Pinto, Karoline Von Ahn; Lund, Rafael Guerra; Martos, Josué (Brazilian Dental Science, 2017)
The generalized presence of stain, particularly on anterior teeth, provides an unaesthetic appearance with a negative impact on the patient. The aim of this paper is to report a case of severe chromatic alterations treated with enamel microabrasion associated with infiltration of low-viscosity resin. The intense brownish pigmentation and white spots of fluorosis lose their whitish appearance and look similar to sound enamel. This association of techniques, which might be an alternative to white-masking of intense pigmentation, showed optimal aesthetic results.